Conversation Analysis of Repair in EFL Classroom - Rifhani Handayani L; Syarifuddin Dollah; Baso Jabu (Har Press Indonesia, 2021)
This research aims to: (1) describe the types of repair occurred during the conversation of the participants in the EFL classroom, (2) disclose the didactic repair occurred during the conversation in EFL classroom, and (3) examine the trouble source in the EFL classroom. This study applied descriptive qualitative method. The participants were the teacher and students at the XII Grade MIPA 1 of SMAN 1 Jeneponto. The research instruments employed in this research were observation and interview. Techniques of data collection were observation (e.g. recording and observational checklist), note-taking technique, and interview. The research findings showed three things. Initially, there were 41 repairs uttered by the participants in the EFL classroom which belonged to four types of repairs, i.e. self-initiated self-repair, self-initiated other repair, other-initiated self-repair, and other initiated other repair. Other-initiated other repair was the most often appearing types of repair, i.e. 22 times. Besides, the didactic repairs were also discovered, including form-and-accuracy (13 times of occurrence), and meaning-and-fluency (16 times of occurrence). However, there were several repairs which were not categorized into any of context of the didactic repair. Therefore, the researcher put them into other items in order to make them well arranged. Next, the common problems appeared within the conversation between teacher and students (or student and student) were mostly about the problem of understanding, then, followed by the linguistics problem of the student, and the technical problem i.e. mishearing and non-hearing.